Microscopic evidence for the dissociation of water molecules on cleaved GaN(11̄00). Issue 2 (18th December 2017) - Wu, Shih-Yu; Lang, Liang-Wei; Cai, Pei-Yang; Chen, Yun-Wen; Lai, Yu-Ling; Lin, Ming-Wei; Hsu, Yao-Jane; Lee, Wei-I; Kuo, Jer-Lai; Luo, Meng-Fan; Kuo, Chien-Cheng
Abstract : The dissociation of water molecules absorbed on a cleaved non-polar GaN(11̄00) surface was studied primarily with synchrotron-based photoemission spectra and density-functional-theory calculations. Abstract : The dissociation of water molecules absorbed on a cleaved non-polar GaN(11̄00) surface was studied primarily with synchrotron-based photoemission spectra and density-functional-theory calculations. The adsorbed water molecules are spontaneously dissociated into hydrogen atoms and hydroxyl groups at either 300 or 130 K, which implies a negligible activation energy (<11 meV) for the dissociation. The produced H and OH were bound to the surface nitrogen and gallium on GaN(11̄00) respectively. These results highlight the promising applications of the non-polar GaN(11̄00) surface in water dissociation and hydrogen generation.